Pakistan Army Green Book 2014 - Pakistan Army; Edited by Ikram Ul Haq, Lt. Gen. ; Lodhi, Naeem Khalid, Lt. Gen. ; Ghulam Qamar, Maj. Gen. ; Firdous, Nayyer, Brigador Dr. ; Naeem Haider, Brid. Dr. (GHQ, Rawalpindi Pakistan Army, 2014)
The Contents of this Book are Writers' Personal Views. The Statements, Facts and opinions by the authors in the green book do npt imply the offical policy of the institution, editors or the Publishers.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals